Role of hyperbaric oxygen therapy in the treatment of periodontitis - Ravi Prakash Popat; Parita Ravi Popat (SRM Journal of Research in Dental Sciences, 2014)
Periodontitis is a multifactorial disease caused by pathogenic microorganisms but modified by host response and environmental factors. Most of microorganisms responsible for periodontal destruction are obligatory or facultative anaerobes. Hyperbaric oxygen therapy (HBOT) includes therapeutic administration of 100% oxygen under pressure, which has a deleterious effect on anaerobic microorganisms responsible for periodontal diseases. This review focuses on the role of HBOT as a therapeutic measure for individual with periodontal diseases.